The effect of 5% Curcuma xanthorrhiza extract gel on diabetic rat socket: A fibroblast analysis - Anggayanti, Nyoman Ayu; Purbasari, I Gusti Ayu Kade Ira; Wahyuni, Putu Sinta Elix (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2024)
Background: Predominant advanced glycation end products (AGEs) in diabetes mellitus (DM) patients lead to increased reactive oxygen species, causing oxidative stress and cell apoptosis, which hinders wound healing. Curcuma xanthorrhiza contains active compounds such as curcumin, flavonoids, and saponins, which can increase fibroblast cell production, the primary indicator of wound healing, and serve as AGE inhibitors. Purpose: This study aimed to determine the effect of 5% C. xanthorrhiza extract gel on the number of fibroblasts in diabetic Wistar rats during the healing of tooth extraction over a specific duration. Methods: The left mandibular incisor was extracted after using alloxan to induce diabetes in the rats. The socket was then treated with different compounds, including 5% C. xanthorrhiza extract gel, placebo CMC-Na, or Gengigel. A histopathological examination of the socket was conducted to assess the presence of fibroblasts on days one, three, and five after treatment. Results: The number of fibroblasts in the sockets treated with 5% C. xanthorrhiza extract gel was lower than in the Gengigel group but higher than in the placebo group (p < 0.05). Conclusion: 5% C. xanthorrhiza extract gel can increase the number of fibroblasts, thereby potentially accelerating wound healing in DM.